Doctors, Patients and the Constitution: A Theoretical Analysis of the Physician's Role in “Private” Reproductive Decisions - Susan Frelich Appleton (Washington University Law Quarterly, 1985)
This Article examines the role of the physician and current medical practice in the changing legal status of abortion restrictions. In doing so, this Article considers "constitutional privacy" from a perspective different from other inquiries, which almost always emphasize the individual patient as the right-holder, and concludes that, at least in the abortion context, the Court's vision of privacy consistently makes the doctor, not his patient, the centerpiece of the analysis.
Keywords: Abortion; Right of privacy; Physicians